MCTS Self-Paced Training Kit (Exam 70-526): Microsoft .NET Framework 2.0 Windows-Based Client Development - A.stoecker Matthew (Microsoft Press, 2006)
Ace your exam preparation and ramp up quickly on using the .NET Framework for Windows-based client development by working at your own pace through the lessons, hands-on exercises, and practice tests. The CD features 425 practice questions and a best-of-class test engine with pre-assessment and post-assessment capabilities. Choose timed or untimed testing mode, generate random tests, or focus on discrete objectives or chapters, and get detailed explanations for right and wrong answers?including pointers back to the book for further study. You also get a 90-day evaluation version of Microsoft Visual Studio® 2005 software and a 15 percent exam discount voucher—making this kit an exceptional value and a great career investment.